(untitled) (Politeja, 2025)
The paper discusses anti-immigrant rhetoric in three countries: the United Kingdom, Ireland and Sweden, covering the period of 2020 – 2024. Based on an in-depth analysis of the statements issued by leading politicians of the countries and civic expressions in the form of protests and demonstrations, some common traits can be identified as leading motives in the public populistic discourse. The three shades of populism have, however, their distinctions stemming from cultural, political and economic specifics of the countries. Deconstructing of the internal pattern of the populistic discourse may help liberal democracies respond effectively to the challenges posed by simplistic and thus often misleading rhetoric.